Schonbrunn palace viewed from the garden - Henshall, Josiah (engraver):::Creator::::::::::::; Batty, Robert, 1789-1848 (artist):::Contributor:::::::::::: (Rodwell & Martin ; printed by McQueen & Co.; United Kingdom; London)
Engraving of Schonbrunn Palace viewed from the garden, Vienna